2022
DOI: 10.1016/j.chb.2021.107174
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fake news rebuttal acceptance during the COVID-19 pandemic and the moderating effect of cognitive ability

Abstract: Fake news is spreading rapidly on social media and poses a serious threat to the COVID-19 outbreak response. This study thus aims to reveal the factors influencing the acceptance of fake news rebuttals on Sina Weibo. Drawing on the elaboration likelihood model (ELM), we used text mining and the econometrics method to investigate the relationships among the central route (rebuttal's information readability and argument quality), peripheral route (rebuttal's source credibility, including authority and influence)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 131 publications
2
35
0
Order By: Relevance
“…Therefore, an individual can easily acquire accurate information, which can help them adjust to new thoughts and the CECC's recommended actions to prevent COVID-19. This finding is consistent with those of other studies (e.g., Barreda-Ángeles & Hartmann, 2022 ; Qazi et al, 2020 ; Song et al, 2021 ; Wang et al, 2022 ), which have revealed that the development of situational awareness during public health crises based on formal information sources facilitates the adoption of appropriate preventive behavior, which can limit the spread of infectious diseases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, an individual can easily acquire accurate information, which can help them adjust to new thoughts and the CECC's recommended actions to prevent COVID-19. This finding is consistent with those of other studies (e.g., Barreda-Ángeles & Hartmann, 2022 ; Qazi et al, 2020 ; Song et al, 2021 ; Wang et al, 2022 ), which have revealed that the development of situational awareness during public health crises based on formal information sources facilitates the adoption of appropriate preventive behavior, which can limit the spread of infectious diseases.…”
Section: Discussionsupporting
confidence: 92%
“… Bronfman et al (2021) noted that attitudes, social norms, perceived behavioral control, and knowledge levels regarding COVID-19, are critical predictors of an individual's preventive behavior. Dai et al (2020) discovered that constructive risk communication and comprehensive pandemic information had stronger effects on preventive behavior than did rumor refutation and fake news (Li, Cui, Kaminga, Cheng, & Xu, 2022; Luo, Wang, Guo, & Luo, 2021 ; Wang, Chao, Yu, & Zhang, 2022 ). Liu (2020) validated mediating pathways regarding different types of digital media consumption to preventive behaviors and showed that COVID-19-related information across digital media directly influenced preventive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study has explored the factors influencing the acceptance of fake news rebuttals, demonstrating that the source authority had a negative effect on rebuttal acceptance, while source influence had a positive effect. Moreover, the authors highlight how information readability and argument quality positively affected rebuttal acceptance [ 46 ]. However, in a social network like Facebook, both readability and argument quality are very difficult to offer because of the structure of the social network and why people spend few seconds reading (about 15 s), and as stated by the CEO of Chartbeat (a company that provides companies with real-time data to understand reader behavior): “we confuse what people have clicked on for what they have read and understood” [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that individuals with low cognitive abilities relied more on source credibility and argument quality to accept fake news rebuttal [ 46 ], a fact that once again underlines the importance and quality of information sources. Facebook, Twitter, and YouTube issued a joint statement that stated they are “[…] jointly combating fraud and misinformation about the virus, elevating authoritative content on [their] platforms” [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, social media news use has been linked to COVID-19 vaccine hesitancy, which is a key issue for policy makers worldwide [ 40 ]. Second, while rare investigations have focused on the role of personality traits in COVID-19 misinformation engagement on social media [ 36 , 41 ], it has not been studied in conjunction with cognition or cognitive ability, another important factor related to individual engagement with misinformation [ 42 ]. Prior research has argued that people with certain personality traits and cognitive ability may engage with misinformation.…”
Section: Introductionmentioning
confidence: 99%